OUTCOME ANALYSIS OF PRIMARY CHEST WALL TUBERCULOSIS: A SERIES OF 32 CASES - Majeed, Farhan Ahmed; Ali, Ahmad; Zafar, Usama; Taimure, Siemel Zia Ahmed; Mahmood, Umer (Journal of Ayub Medical College Abbottabad, 2021)
Background: Chest wall tuberculosis is a rare disease, and although incidence has decreased further with advances in antituberculosis chemotherapy, it remains prevalent in developing countries. Diagnosis is difficult because pus smears or bacterial cultures of aspirate frequently fail to yield tuberculous bacilli. To discuss the characteristics of this rare disease and suggest an optimal strategy for management, we share our experience with 32 patients managed surgically and with antituberculosis chemotherapy. Methods: In this descriptive case series we retrospectively reviewed the medical records of 32 patients managed from May 2006 to May 2016. Results: Out of 32 cases of chest wall tuberculosis, 59.4% (n=19) patients had a current or previous history of tuberculosis. Presenting complaints were chest pain, a palpable mass and pus discharge in most patients. A preoperative bacteriologic diagnosis was positive in only 3 patients. Generous abscess debridement was done in 21 (65.63%) cases, abscess debridement and partial rib resection in 11 (34.38%), abscess debridement and partial sternum excision in 7 (21.88%), and clavicle excision in 2 (6.25%) patients. Postoperative wound infection was noted in 1 (3.13%) patient. There were no recurrences. Conclusion: Chest wall tuberculosis requires generous debridement of diseased tissue including under lying bone, meticulous obliteration of residual dead space by vascular muscle flap, and negative suction drainage in addition to antituberculosis chemotherapy for good post-operative results with acceptable morbidity and mortality